2020
DOI: 10.2176/nmc.oa.2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Functional Outcomes for World Federation of Neurosurgical Societies Grade V Aneurysmal Subarachnoid Hemorrhage after Active Treatment

Abstract: This study investigated the long-term outcomes of patients with World Federation of Neurosurgical Societies (WFNS) grade V aneurysmal subarachnoid hemorrhage (SAH) who underwent early aneurysm repair. We evaluated consecutive patients with WFNS grade V aneurysmal SAH from April 2010 to March 2015 who underwent aneurysm repair within 72 h after onset. We assessed the functional outcomes at discharge and 3 years after onset using the modified Rankin Scale (mRS). The primary outcome was defined as a favorable fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…46 Other studies have variably reported that high mean transit time on CT perfusion scans, evidence of early ischemic changes on CT angiography, absent corneal reflexes, and vasospasm-induced infarction are also highly predictive of poor outcome. 5,9,12,47 In keeping with our results, several studies indicate that even ominous admission characteristics, such as absent pupillary light reactivity or pre-hospital cardiac arrest, do not have sufficient PPV to predict hopeless outcome.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…46 Other studies have variably reported that high mean transit time on CT perfusion scans, evidence of early ischemic changes on CT angiography, absent corneal reflexes, and vasospasm-induced infarction are also highly predictive of poor outcome. 5,9,12,47 In keeping with our results, several studies indicate that even ominous admission characteristics, such as absent pupillary light reactivity or pre-hospital cardiac arrest, do not have sufficient PPV to predict hopeless outcome.…”
Section: Discussionsupporting
confidence: 88%
“…Patients were mechanically ventilated for a median of 7 (2-13) days. ICU and hospital (including in-patient neurorehabilitation) length of stay were 12 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and 76 (26-118) days, respectively.…”
Section: Characteristics Of Wfns Grade 5 Patients With Favorable Outcomes (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…10,13 Conversely, several reports have revealed that some of patients have good outcomes. 9,[11][12][13][14] It is still unclear which factors develops this heterogeneity in their outcomes. However, our decision tree model, OPAS-V, based on the routine examinations including laboratory findings at admission may be useful in identifying patients who need aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Conversely, several reports have revealed that 14-25% of aggressively treated patients with WFNS grade V aSAH had good outcomes. 9,[11][12][13][14] The clinical severity of aSAH at admission has been reported to reflect the acute inflammatory response, including early brain injury (EBI). [15][16][17] In patients with WFNS grade V, the impact of EBI on their outcomes may be heterogeneous 16,18 and should be considered when developing outcome prediction models.…”
Section: Introductionmentioning
confidence: 99%